PRODUCT STANDARDIZATION AT KRS - Cheryl Marlitta Stefia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
In Indonesia, the food industry is one of the sectors that support the increase inthe value of the national investment, the Ministry of Industry noted, throughout2018, the food and beverage industry can grow 7.91% or exceed the nationaleconomic growth of 5.17%. According to the Indonesian Franchise Association,this food industry trend is in line with the increasing interest in franchising.Encouraged to participate in advancing the Indonesian economy, KRS seeks toundertake all franchise offers submitted by loyal KRS customers. There are 19franchise offers throughout Indonesia. Accepting challenges in developingbusiness, KRS wants to ensure that products from KRS are well standardized sothat it does not damage the excellent image that KRS has built. Therefore, thepurpose of this research is to know and implement standardization procedures forproducts to maintain uniformity of quality wherever KRS products are soldthroughout Indonesia.The approach that will be used in this study begins with aninternal analysis consisting of the VRIO Framework and Value Chain. Afterconducting an internal analysis, the research will proceed with analyzing externalproblems, namely Porter 5 forces and PESTLE. TOWS Matrix, Value Proposition,and SIPOC to Lean Six Sigma with DMAIC tools as a combination of Six Sigmaand Lean concepts. The main causes of problems faced by KRS are the poorperformance of part-workers, ineffective distribution of information, and verymanual and administrative processes that are very ineffective andinefficient.Solutions and improvements that can be applied to improve theefficiency of the operation process are the creation of an E-Operation application,the benefits to be gained include increased transparency and accountability,integration of all the divisions involved and access tracking in real-time. Trainingand contract binding can be done to improve the human resource division, andfinally, the solution offered to address the problem of information distribution isto fill vacant positions, namely the coordinator who mediates between the centralkitchen and the part workers